Two-grid hp-DGFEM for second order quasilinear elliptic PDEs based on an incomplete Newton iteration - Congreve, Scott; Houston, Paul (2013)
In this paper we propose a class of so-called two-grid hp-version discontinuous Galerkin finite element methods for the numerical solution of a second-order quasilinear elliptic boundary value problem based on the application of a single step of a nonlinear Newton solver. We present both the a priori and a posteriori error analysis of this two-grid hp-version DGFEM as well as performing numerical experiments to validate the bounds.